Dielectric Properties of Pure and Gd‐Doped HfO2 Ceramics. Issue 12 (2nd September 2015) - Wang, Chunchang; Zhang, Da; Wang, Hong; Yu, Yi; Li, Yide; Li, Qiuju
Abstract : The pure, 2 at.%, and 20 at.% Gd‐doped HfO2 ceramics were prepared by the standard solid‐state reaction technique. Dielectric properties of these ceramics were investigated in the temperature range 300–1050 K and frequency range 20–5 × 10 6  Hz. Our results revealed an intrinsic dielectric constant around 20 in the temperature below 450 K for all tested ceramics. Two oxygen‐vacancy‐related relaxations R1 and R2 were observed at temperatures higher than 450 K, which were identified to be a dipolar relaxation due to grain response and a Maxwell–Wagner relaxation due to grain‐boundary response, respectively. The dielectric properties of the pure and slightly doped (2 at.%, ) samples are dominated by the grain‐boundary response, which results in a colossal dielectric behavior similar to that found in CaCu3 Ti4 O12 . The doping level of 20 at.% leads to the structural transformation from monoclinic phase to cubic phase. The dielectric properties of the heavily doped HfO2 are dominated by the grain response without any colossal dielectric behavior.